Multilanguage design of heterogeneous systems - Coste, P.; Hessel, F.; Le Marrec, Ph; Sugar, Z.; Romdhani, M.; Suescun, R.; Zergainoh, N.; Jarraya, A. A. (Hardware/Software Codesign 1999: Proceedings of the IEEE 7th International Conference, 1999)
Multilanguage solutions are required for the design of heterogeneous systems where different parts belong to different application classes, e.g. control/data or continuous/discrete. The main problem that needs to be solved when dealing with multilanguage design is the refinement of communication between heterogeneous subsystems. This paper discusses the basic concepts of multilanguage design and introduces MUSIC a multilanguage design approach. The paper also shows the application of this approach in the case of a mechatronic system.